Assessment of Psychopathological Changes and Mental Functioning in Patients with Multiple Sclerosis – a Literature Review - Adam Pawlak; Karina Marciniec; Zuzanna Szczypińska (Pielęgniarstwo Neurologiczne i Neurochirurgiczne, 2023)
MS (Multiple sclerosis) is the most common primary disease of the central nervous system. Although neurological symptoms predominate, an increased incidence of mental health disorders is also observed. The most common are depression and anxiety disorders. Cognitive impairment occurs in half of MS patients. Most often, they are associated with difficulties in concentration, memory disorders, and slower information processing. Changes occurring in the CNS cause long-term chronic fatigue. The loss of sexual drive may be caused by CNS pathology, especially the limbic system and brain stem nuclei, or by psychological mechanisms in response to the impact of MS symptoms. Pain is very troublesome for patients and makes it difficult to function, disturbing the quality of sleep, negatively affecting mood, causing anxiety and depression. A complete understanding of all aspects of MS in the bio-psycho-social dimension is necessary to provide holistic care to a patient with MS. The knowledge of medical staff regarding the image of psychopathological changes in the course of MS may be of great importance for the proper assessment of the mental state of patients and for undertaking adequate medical and nursing interventions. This will undoubtedly contribute to reducing psychopathological symptoms in patients themselves and thus improving the quality of life. (JNNN 2023;12(4):177–182)